2009
DOI: 10.1373/clinchem.2009.124370
|View full text |Cite
|
Sign up to set email alerts
|

Serum Free Light Chain Ratio, Total κ/λ Ratio, and Immunofixation Results Are Not Prognostic Factors after Stem Cell Transplantation for Newly Diagnosed Multiple Myeloma

Abstract: Background: The prognostic value of changes in paraprotein markers after stem cell transplantation is unknown. We evaluated disease response using serum immunofixation (s-IFIX), total κ and λ ratio (KLR), and free light chain (FLC) ratio in myeloma patients who underwent autologous or autologous plus allogeneic stem cell transplantation. Methods: We studied s-IFIX, KLR, and FLC ratio in sera from 203 patients, 3 months after transplantation. We evaluated overall and event-free survival (OS and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 30 publications
4
26
1
1
Order By: Relevance
“…However, the evaluation was in MM patients who had undergone ASCT and ASCT with allogeneic stem cell transplantation (allo-HCT), which precluded one to one comparison between the 2 studies. 23 Different from our study, Iwama et al showed that normalization of sFLC k/l ratio after treatment was associated with superior OS and We also demonstrated that i/u sFLC ratio > 10 was an independent predictor of shorter OS (97.4% vs. 55.8%) in MM patients. There is not an established cutoff point for the reduction in sFLC ratio after treatment that determines the prognosis.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…However, the evaluation was in MM patients who had undergone ASCT and ASCT with allogeneic stem cell transplantation (allo-HCT), which precluded one to one comparison between the 2 studies. 23 Different from our study, Iwama et al showed that normalization of sFLC k/l ratio after treatment was associated with superior OS and We also demonstrated that i/u sFLC ratio > 10 was an independent predictor of shorter OS (97.4% vs. 55.8%) in MM patients. There is not an established cutoff point for the reduction in sFLC ratio after treatment that determines the prognosis.…”
Section: Discussioncontrasting
confidence: 94%
“…22 Later on, the prognostic significance of sFLC response after the treatment has been investigated in various studies. 18,23,24 In this study, we investigated the predictive value of sFLC response on disease course during the early phase of CT in MM patients. We used the normalization of sFLC k/l ratio and i/u sFLC ratio > 10 and < 10 for the evaluation of sFLC response.…”
Section: Discussionmentioning
confidence: 99%
“…1,18 Because the sFCL test is insensitive to the monoclonal or polyclonal nature of light chains, and the ratio k/l is frequently altered by the oligoclonal bands 19 that emerged in the context of immune regeneration, 20 the lack of clinical relevance of k/l ratios reported herein is not surprising and agrees with previous observations. [9][10][11]21 However, the absence of significant differences for TTP and OS between patients in stringent vs conventional CR differs from that reported by Kapoor et al,8 which showed highly significantly survival benefit for patients in sCR compared with those in conventional CR. Although the number of patients in this study and follow-up of both series are similar, unfortunately, the Kapoor et al study does not mention the individual contribution of the sFLC ratios or BM clonality assessments to understand the origin of the discordant results.…”
Section: Resultsmentioning
confidence: 91%
“…7 Despite its wide use as a clinical end point, only 1 study 8 has reported a benefit of sCR over CR, whereas other studies suggested that the k/l values do not provide additional prognostication. [9][10][11] Furthermore, the term sCR is widely used without a clear description of how BM clonality was evaluated, nor the individual influence of the sFLC and BM clonality to define sCR criteria. Here, we report on the value of achieving sCR among patients in conventional CR included in 2 consecutive Grupo Español de Mieloma Múltiple/Programa para el Estudio de la Terapéutica en Hemopatías Malignas (GEM/PETHEMA) clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Though normalization of serum immunofixation and kappaelambda ratio (KLR) correlated, a normal KLR was not associated with prolonged progression-free survival (PFS) or overall survival (OS). 21 In contrast, Mori et al studied 73 patients and found that relative to bone marrow aspiration and biopsy, the addition of FLC to M-spike at diagnosis and after induction with novel therapies (and before SCT) improved the accuracy of response assessment, including associated improvements in PFS and OS after SCT. 22 The reason for the disagreement in these 2 studies is unclear but may be related to different induction regimens or timing of FLC measurement (VAD vs. novel agents and 3 months after SCT vs. before SCT, respectively).…”
Section: Introductionmentioning
confidence: 99%